The first case report of failed single-anastomosis-duodeno-ileal bypass converted to One anastomosis gastric bypass/Mini-gastric bypass - Chiappetta, Sonja (Int J Surg Case Rep, 2017)
INTRODUCTION: The established single-anastomosis-duodeno-ileal bypass with sleeve gastrectomy (SADI-S) is based on a sleeve gastrectomy (SG) as the restrictive part of the procedure. Due to preserved pylorus, SG has the disadvantage of a high-pressure system with de novo or worsening of existing gastroesophageal reflux disease (GERD). CASE PRESENTATION: A female patient presented herself due to protracted GERD and weight regain after multiple bariatric surgeries. At an initial weight of 158 kg (BMI 62.5 kg/m(2)) the patient underwent adjustable gastric banding in 2009. After band removal in slippage, the patient underwent SG at a weight of 135 kg in 2012. Nine months after SG, SADI-S was performed as a malabsorptive second step procedure. After 32 months the patient suffered from severe GERD under proton pump inhibitor therapy. Actual weight was 107.9 kg (BMI 42.7 kg/m(2)). Upper endoscopy showed a hiatal hernia and esophagitis B and dorsal hiatoplasty was performed. After 6 months in still existing severe GERD and weight regain indication for laparoscopic conversion to One anastomosis gastric bypass/Mini-gastric bypass (OAGB/MGB) was given, aiming to reduce the high-pressure system of SG in a low-pressure system of OAGB/MGB. One year after revisional surgery reflux was reported to be only occasionally. Further weight loss was seen (91 kg, BMI 36 kg/m(2), EWL 67.7%). CONCLUSION: SG as the restrictive part of SADI-S may lead to GERD and consequently to pathologic eating of “soft” calories, that defeats the operation and results in weight regain. OAGB/MGB might be a simple method to rescue such failed SADI-S patients.